Finding cultural heritage images through a Dual-Perspective Navigation Framework. Issue 5 (September 2016) - Lin, Yi-Ling; Brusilovsky, Peter; He, Daqing
Highlights: The framework, DPNF, seamlessly combines faceted browsing and tag-based navigation. DPNF integrates experts' subject headings and social tags. DPNF offers a more efficient, effective, and user-oriented interface than single ones. Abstract: With the increasing volume of digital images, improving techniques for image findability is receiving heightened attention. The cultural heritage sector, with its vast resource of images, has realized the value of social tags and started using tags in parallel with controlled vocabularies to increase the odds of users finding images of interest. The research presented in this paper develops the Dual-Perspective Navigation Framework (DPNF), which integrates controlled vocabularies and social tags to represent the aboutness of an item more comprehensively, in order that the information scent can be maximized to facilitate resource findability. DPNF utilizes the mechanisms of faceted browsing and tag-based navigation to offer a seamless interaction between experts' subject headings and public tags during image search. In a controlled user study, participants effectively completed more exploratory tasks with the DPNF interface than with the tag-only interface. DPNF is more efficient than both single descriptor interfaces (subject heading-only and tag-only interfaces). Participants spent significantly less time, fewer interface interactions, and less back tracking to complete an exploratory task without an extra workload. In addition, participants were more satisfied with the DPNF interface than with the others. The findings of this study can assist interface designers struggling with what information is most helpful to users and facilitate searching tasks. It also maximizes end users' chances of finding target images by engaging image information from two sources: the professionals' description of items in a collection and the crowd's assignment of social tags.